Comparison of Serum Inhibin B and Follicle-Stimulating Hormone (FSH) Level between Normal and Infertile Men in Yaoundé - Tchoula Mamiafo Corinne; Pieme Constant Anatole; Ngogang Yonkeu Jeanne (Hindawi Limited, 2020)
Objective. Hormones play a vital role in initiating and maintaining male reproductive function. The present study explores the influence and predictive ability of two reproductive hormones on semen quality among men who were partners in an infertile couple. Design. During our cross sectional study, men were recruited from private and public hospital and laboratories for clinical evaluation of fertility status. Methods. Fresh semen samples were assessed for quality (concentration, motility and morphology) according to the 2010 World Health Organization manual and the serum levels of hormones, including follicle-stimulating hormone (FSH), Inhibin B was measured (ELISA). Results. We found a significant difference in the two groups regarding sperm concentration (p<0.0001), total sperm count (p<0.0001), progressive motility (p<0.0001), vitality (p<0.0001) and the percentage of normal forms (p=0.043). We found a strong and negative correlation between FSH and Inhibin B in the overall population, the normozoospermic reference group and the case group. Our study confirmed that Inhibin B was significantly and positively correlated with sperm concentration and leucocytes, and that FSH was negatively correlated to sperm concentration and vitality. Conclusion. Consistent with other studies, our results show strong association between semen quality and FSH and Inhibin B.